PERAN SANUR BERSATU TRANSPORT TERHADAP MUNCULNYA PARAREM TRANSPORTASI ONLINE DI WILAYAH SANUR - Kharismadiani, Ni Nyoman; Erawan, I Ketut Putra; Mahaswari Jayanthi Mertha, A.A Sagung Mirah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
This study seeks to find out how the role of Sanur Bersatu Transport in the emergence of online transportation pararem in Sanur area. This study uses Castells' theory of identity politics and Caporaso's political economy theory with qualitative research. The results of this study are in interviews with resource persons, authors find namely the role of Sanur Bersatu Transport in the emergence of pararem. The existence of online transportation in the community makes conventional transportation less attractive and feels excluded. Departing from this, Sanur Bersatu Transport also bring up a policy in their environment that is intended for online transportation. The pararem is intended for the benefit of the Sanur community, especially for Sanur residents who work as conventional transportation drivers and are members of the Sanur Bersatu Transport. The existence of pararem regarding online transportation in the Sanur area is an application of Identity Politics and Political Economy. Keywords: transportation, identity politics, political economy and pararem